Предмет:
МатематикаАвтор:
аноним1) Логарифмируем обе части уравнения по основанию 3:
3^x = 5^2;
xlog3(3) = 2log3(5);
x = 2log3(5).
2) Логарифмируем обе части уравнения по основанию 2:
5^x = 8^x;
xlog2(5) = xlog2(8);
xlog2(5) - xlog2(8) = 0;
x(log2(5) - log2(8)) = 0;
x = 0.
3) Логарифмируем обе части уравнения по основанию 3:
4^x =3^x / 3;
xlog3(4) = xlog3(3) - log3(3);
xlog3(4) = x - 1;
x(log3(4) - 1) = - 1;
x = -1 / (log3(4) - 1);
x = 1 / (1 - log3(4)).
Ответ: 1) 2log3(5); 2) 0; 3) 1 / (1 - log3(4)).
Автор:
finnegan55Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть